2005
DOI: 10.1203/01.pdr.0000170899.90479.1e
|View full text |Cite
|
Sign up to set email alerts
|

Hypothermia and Amiloride Preserve Energetics in a Neonatal Brain Slice Model

Abstract: A period of secondary energy failure consisting of a decline in phosphocreatine/inorganic phosphate (PCr/Pi), a rise in brain lactate, and alkaline intracellular pH (pH i ) has been described in infants with neonatal encephalopathy. Strategies that ameliorate this energy failure may be neuroprotective. We hypothesized that a neonatal rat brain slice model undergoes a progressive decline in energetics, which can be ameliorated with hypothermia or amiloride. Interleaved phosphorus ( 31 P) and proton ( 1 H) magne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 57 publications
0
9
0
Order By: Relevance
“…In a tissue culture model of cerebral ischemia, the prevention of rebound alkalosis using amiloride after in vitro HI delayed the onset of injury for as long as the cells remained acidotic (25). Recent studies in an ex vivo model of neonatal rat brain slices demonstrated a preservation of brain slice energetics over several hours in those brain slices exposed to amiloride; this preservation of brain slice energetics with amiloride was similar to that observed in brain slices main- tained under hypothermic conditions (26). Further in vivo studies in neonatal models are required to demonstrate whether amiloride retains its neuroprotective effect when treatment is commenced after HI and whether its neuroprotective effect is enhanced in combination with other strategies such as hypothermia.…”
Section: Discussionmentioning
confidence: 73%
“…In a tissue culture model of cerebral ischemia, the prevention of rebound alkalosis using amiloride after in vitro HI delayed the onset of injury for as long as the cells remained acidotic (25). Recent studies in an ex vivo model of neonatal rat brain slices demonstrated a preservation of brain slice energetics over several hours in those brain slices exposed to amiloride; this preservation of brain slice energetics with amiloride was similar to that observed in brain slices main- tained under hypothermic conditions (26). Further in vivo studies in neonatal models are required to demonstrate whether amiloride retains its neuroprotective effect when treatment is commenced after HI and whether its neuroprotective effect is enhanced in combination with other strategies such as hypothermia.…”
Section: Discussionmentioning
confidence: 73%
“…Interestingly, ATP content in these preparations is apparently the same, either in HEPES-or in bicarbonate-buffered medium [38]. Based on extracellular lactate, it is possible to observe a significant energetic variation during the first hour and a recovery from 1 h on.…”
Section: Discussionmentioning
confidence: 84%
“…During in vitro cerebral ischemia, NHE inhibitors (DMA, harmaline [46], SM-20220 [88], amiloride [89], and HOE-642 [85, 87, 90]) had a protective effect, in terms of delayed pH i normalization both in neuronal cells and in astrocytes [46, 8992], inhibition of microglia [90], and less intracellular calcium accumulation [87, 88]. This anoxia-induced alkalization was also ameliorated in NHE1−/− CA1 neurons.…”
Section: Na+/h+ Exchangersmentioning
confidence: 99%